2016
DOI: 10.21147/j.issn.1000-9604.2016.05.06
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of lymph node number and prognosis in gastric cancer patients with perigastric lymph nodes retrieved by surgeons and pathologists

Abstract: ObjectiveTo compare the numbers of positive and total lymph nodes and prognosis in gastric cancer patients whose perigastric lymph node retrieval was performed by surgeons and pathologists.MethodsWe conducted a retrospective analysis of clinical and follow-up data from 1, 056 patients who underwent gastric cancer D2 radical lymph node resection between January 2008 and December 2010 in the Gastrointestinal Surgery Department of Yantai Yuhuangding Hospital. The follow-up ended in December 2015. Patients were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 18 publications
(10 reference statements)
0
19
0
Order By: Relevance
“…LN retrieval from the operation specimen not by pathologists but by the surgicopathologic team (who have been trained with anatomical and surgical learning programs) can obtain a better three-dimensional view of the anatomical relationships. Furthermore, previous studies have demonstrated that despite some anatomical variability in the distribution of LNs, LN retrieval by the surgicopathologic team, rather than by the pathologists, could lead to more RLNs, which is helpful for standardizing the nodal status assessment (9,21). Consistently, in our trial, the number of RLNs in the surgicopathologist group was significantly higher than that in the pathologist group (18.8 ± 11.5 vs. 53.8 ± 20.9, p < 0.001); the surgicopathologist group also detected a greater number of MLNs (3.9 ± 5.7 vs. 5.6 ± 9.8, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…LN retrieval from the operation specimen not by pathologists but by the surgicopathologic team (who have been trained with anatomical and surgical learning programs) can obtain a better three-dimensional view of the anatomical relationships. Furthermore, previous studies have demonstrated that despite some anatomical variability in the distribution of LNs, LN retrieval by the surgicopathologic team, rather than by the pathologists, could lead to more RLNs, which is helpful for standardizing the nodal status assessment (9,21). Consistently, in our trial, the number of RLNs in the surgicopathologist group was significantly higher than that in the pathologist group (18.8 ± 11.5 vs. 53.8 ± 20.9, p < 0.001); the surgicopathologist group also detected a greater number of MLNs (3.9 ± 5.7 vs. 5.6 ± 9.8, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…The number of RNLs is influenced by the extent of lymphadenectomy, the surgeon's enthusiasm to pathologically examine more LNs, the surgeon's skill, surgical considerations (such as fat volume), and the innate number of LNs in each patient [9][10][11]18]. Depending on the surgeon's skill, LNs may not be completely excised, may be destroyed, or both, which may affect the number of RLNs.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with RLNs < 40, careful and intensive follow-up should be performed, because they are at high risk of disease recurrence. The UICC guidelines recommend radiotherapy and chemotherapy to prevent recurrence in patients with > 16 harvested LNs [11]. Postoperative adjuvant chemoradiation therapy may, therefore, serve as a preferred option to control locoregional recurrence and suitable for evaluating patients with RLNs < 40 after total gastrectomy, though this is not been proven to confer a survival benefit upon patients from Asian countries [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations